The absence of effect of ganglionated plexi ablation on heart rate variability parameters in patients after thoracoscopic ablation for atrial fibrillation - Zdarska, Jana; Osmancik, Pavel; Budera, Petr; Herman, Dalibor; Prochazkova, Radka; Talavera, David; Straka, Zbynek (Journal of thoracic disease, 2017)
BACKGROUND: Hybrid ablation [thoracoscopic ablation (TA) of atrial fibrillation (AF) followed by catheter ablation (CA)] is an increasingly common method of the treatment for patients with AF. The aim of this study was to assess the response to ganglionated plexi (GP) ablation in patients with a previous TA (i.e., to assess whether TA had resulted in damage to the GP. Heart rate variability (HRV) was used as a marker of the autonomic response. METHODS: Twenty AF patients underwent pulmonary vein isolation (PVI) plus GP ablation (GP group) and 18 AF patients underwent CA including GP ablation as a part of hybrid ablation (i.e., all patients had undergone a previous TA; Hybrid group). In each group, a 5 min electrocardiogram (ECG) obtained before and after the CA were analyzed. Time and frequency domain parameters were evaluated. RESULTS: Vagal responses (VR) during CA were observed in 12 (60%) patients in the GP group; however, in the Hybrid group, VR was not observed in any of the patients during CA. The change in normalized power in the low frequency (LF) component and the ratio between the LF and high frequency (LF/HF ratio) components of the HRV spectra, before and after ablation, were statistically significant in the GP group (3.3±2.6 before vs. 1.8±1.9 after ablation) but unchanged, before or after CA, in the Hybrid group. CONCLUSIONS: GP ablation in patients subsequent to TA has a little influence on HRV parameters, which could be explained by GP damage during the preceding TA.
Keywords: hybrid ablation; Ganglionated plexi (GP); heart rate variability (HRV); atrial fibrillation (AF)